Receipt of help by people with cognitive impairment: results from the English Longitudinal Study of Ageing. (1st February 2023) - Read, Sanna; Hu, Bo; Dixon, Josie; Brimblecombe, Nicola; Wittenberg, Raphael; Brayne, Carol; Banerjee, Sube
Abstract: Objectives: We investigated whether people with dementia or low memory/orientation reported more help misaligned with needs – more unmet need and/or more unrequired help – than other people with similar levels of functional limitation, and examined associations with quality of life. Methods: From pooled English Longitudinal Study of Ageing data from waves 6, 7, and 8, we identified community-dwelling people aged 50+ with: dementia ( n = 405); low memory/orientation but no dementia ( n = 4520); and intact memory/orientation ( n = 10, 264). Unmet need (not receiving help for the functional limitation) and unrequired help (receipt of help without the respective functional limitation) were used as outcomes in two-part regressions. Quality of life (CASP-19) was used as a continuous outcome in a linear regression. Functional limitation and its interaction with cognitive status and socio-demographic factors were included in the models. Results: Those with dementia or low memory/orientation but few functional limitations reported more unmet needs and unrequired help than their counterparts with intact memory/orientation. At high levels of limitations, the needs of those with dementia or lower memory/orientation were met more often and the receipt of unrequired help was similar compared to those with intact memory/orientation. Unmet need and unrequired help were associated with poorer quality of life. Conclusions: Unmet need and unrequired help were particular challenges for those with poorer cognition and potentially at early stages of dementia; they were associated with lower quality of life. Our results highlight the importance of good-quality timely diagnosis, identification of needs, and person- centred assessment to help improve quality of life.